2022
DOI: 10.1093/carcin/bgac043
|View full text |Cite
|
Sign up to set email alerts
|

CSF-1R inhibitor, pexidartinib, sensitizes esophageal adenocarcinoma to PD-1 immune checkpoint blockade in a rat model

Abstract: Esophageal adenocarcinoma (EAC) is a leading cause of cancer deaths. Pexidartinib, a multi-gene tyrosine kinase inhibitor, through targeting CSF-1R, down modulates macrophage mediated pro-survival tumor signaling. Previously, CSF-1R inhibitors have successfully shown to enhance antitumor activity of PD-1/PD-L1 inhibitors by suppressing tumor immune evasion, in solid tumors. In this study, we investigated the antitumor activity of pexidartinib alone or in combination with blockade of PD-1 in a de novo EAC rat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…In Phase I clinical trial, Pexidartinib was combined with sirolimus for the treatment of unresectable Sarcoma and Malignant Peripheral Nerve Tumors ( Manji et al, 2021 ). Pexidartinib was also combined with other anti-tumor drugs like PD-1 checkpoint to approach a better outcome, in Esophageal adenocarcinoma rat model, the use of pexidartinib can improve the efficacy of PD-1 immune checkpoint, Endpoint tissue gene expression results showed that transcription levels of both TGFβ and Arg1 were significantly decreased, which was consistent with our results ( Omstead et al, 2022 ). Novel drug release strategies have also been reported to improve the effect of pexidartinib combined with PD-1 treatment ( Li et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…In Phase I clinical trial, Pexidartinib was combined with sirolimus for the treatment of unresectable Sarcoma and Malignant Peripheral Nerve Tumors ( Manji et al, 2021 ). Pexidartinib was also combined with other anti-tumor drugs like PD-1 checkpoint to approach a better outcome, in Esophageal adenocarcinoma rat model, the use of pexidartinib can improve the efficacy of PD-1 immune checkpoint, Endpoint tissue gene expression results showed that transcription levels of both TGFβ and Arg1 were significantly decreased, which was consistent with our results ( Omstead et al, 2022 ). Novel drug release strategies have also been reported to improve the effect of pexidartinib combined with PD-1 treatment ( Li et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…CSF-1R inhibitor overcome the resistance to PD-1/PD-L1 axis blockade in an esophageal adenocarcinoma model, resulting in enhanced T cells infiltration and reduced M2 macrophage polarization in the TIME. It confirms that the direct translation of TAM suppression into clinical benefit ( 217 ). Emactuzumab, an anti-CSF-1R antibody, has a manageable safety profile in combination with atezolizumab over atezolizumab monotherapy.…”
Section: Combination Therapysupporting
confidence: 76%
“…At present, CSF1R inhibitors in combination with chemotherapy have been tried in clinical trials in some cancers, such as localized prostate cancer and orthotopic glioblastoma ( 49 , 50 ). In addition, blocking CSF1/CSF1R can improve the efficacy of a variety of immunotherapies, including CD-40 agonists ( 51 ) and PD-1 inhibitors ( 52 ).…”
Section: Targeting Macrophages In the Tumor Microenvironmentmentioning
confidence: 99%